High-Throughput Screening of Entamoeba Identifies Compounds Which Target Both Life Cycle Stages and Which Are Effective Against Metronidazole Resistant Parasites - Gretchen M. Ehrenkaufer (Frontiers in Cellular and Infection Microbiology, 2018)
Neglected tropical diseases, especially those caused by parasites, are significantly underserved by current drug development efforts, mostly due to the high costs and low economic returns. One method for lowering the costs of drug discovery and development for these diseases is to repurpose drugs developed for other indications. Here, we present the results of a screen of five repurposed drug libraries to identify potential new lead compounds to treat amebiasis, a disease that affects tens of millions of people and causes ~100,000 deaths annually. E. histolytica, the causative agent of amebiasis, has two major life cycle stages, the trophozoite and the cyst. The current primary treatment for amebiasis, nitroimidazole compounds, do not eliminate parasites from the colonic lumen, necessitating a multi-drug treatment regimen. We aimed to address this problem by screening against both life stages, with the aim of identifying a single drug that targets both. We successfully identified eleven compounds with activity against both cysts and trophozoites, as well as multiple compounds that killed trophozoites with improved efficacy over existing drugs. Two lead compounds (anisomycin and prodigiosin) were further characterized for activity against metronidazole (MNZ) resistant parasites and mature cysts. Anisomycin and prodigiosin were both able to kill MNZ resistant parasites while prodigiosin and its analog obatoclax were active against mature cysts. This work confirms the feasibility of identifying drugs that target both Entamoeba trophozoites and cysts, and is an important step toward developing improved treatment regimens for Entamoeba infection.